Influence of Workplace Technology on Job Skill in selected Food and Beverage Firms in Lagos, Nigeria - Adeniyi , Idowu Sulaimon; Omolawal, Samuel Ayodeji (Journal of Applied And Theoretical Social Sciences, 2024)
This article was published by mistake without an ethical committee approval even though the TR Dizin Index rules require such a report. For this reason, the article was decided to be retracted from publication. JATSS Editorial Team 23.03.2025